2015
DOI: 10.1016/j.biortech.2015.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Multi-system Nernst–Michaelis–Menten model applied to bioanodes formed from sewage sludge

Abstract: Bioanodes were formed under constant polarization at -0.2 V/SCE from fermented sewage sludge. Current densities reached were 9.3±1.2 A m(-2) with the whole fermented sludge and 6.2±0.9 A m(-2) with the fermented sludge supernatant. The bioanode kinetics was analysed by differentiating among the contributions of the three redox systems identified by voltammetry. Each system ensured reversible Nernstian electron transfer but around a different central potential. The global overpotential required to reach the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Other studies have also shown Ignavibacteria spp. to be relatively abundant in anode biofilms (Yoshizawa et al, 2014;Rimboud et al, 2015;Tian et al, 2015;Baek et al, 2016). Our findings of Ignavibacteria genomes rich in large MHCs and porin-cytochrome gene clusters (Figure 3 and Table 3) add further support for EET by members of this group.…”
Section: Discussionsupporting
confidence: 57%
“…Other studies have also shown Ignavibacteria spp. to be relatively abundant in anode biofilms (Yoshizawa et al, 2014;Rimboud et al, 2015;Tian et al, 2015;Baek et al, 2016). Our findings of Ignavibacteria genomes rich in large MHCs and porin-cytochrome gene clusters (Figure 3 and Table 3) add further support for EET by members of this group.…”
Section: Discussionsupporting
confidence: 57%
“…Cyclic voltammograms were performed after the electrodes reached J max , on day 6. For comparison the theoretical curve, corresponding to the Nernst-Michaelis-Menten kinetics [41,42], was added:…”
Section: Effect Of Micro-roughness On Electroactivity Establishment Amentioning
confidence: 99%
“…The bioanodes formed at 40 C displayed two clear peaks, centred at around À0.34 and À0.20 V/SCE (solid line, Fig. 4C), and a shoulder around À0.43 V/SCE which can be interpreted as three redox systems being involved in the electron transfer mechanism [67]. In contrast, the bioanodes formed at 25 C showed only the peak centred at À0.35 V/SCE (Fig.…”
Section: à2mentioning
confidence: 87%